Factors Associated With Atopic Dermatitis In Elementary School Children In Suburban Area In Indonesia: Original Research - Gunawan, Catherine; Satriajaya, Anthony; Vatvani, Akhil Deepak; Waren, Kalis; Angela, Angela; Broto, Resza; Kalumpiu, Jane Florida; Tan, Sylvia (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: There was limited data of Atopic Dermatitis (AD) prevalence and its associated factors in Indonesia. Therefore, the aim of this study was to identify and evaluate the AD prevalence and factors associated with AD in elementary school children in suburban area in Banten.Methods: A cross-sectional study was conducted in 3 elementary schools children age 6 - 7 years old who were randomly selected. Information was obtained through an Indonesian version of the International Study of Asthma and Allergies in Childhood questionnaire (ISAAC).Results: From 304 school children in semi-urban area, AD was reported as ever had an itchy rash which was reccurent for at least 6 months in 17.4% of the children, 19.5% of the children had this itchy rash at any time in the past 12 months, and 11.4 % reported doctor-diagnosed AD. The factors found to be associated with an increased risk of AD were allergic rhinitis (OR 2.151 CI: 1.086-4.261), history of premature birth (<37 weeks) (OR 5.306, CI:1.577-17.858), exclusive breastfeeding (OR 3.126 CI:1.314-7.439), and food allergy (OR 2.912 CI:1.386-6.119).Conclusion: The results of this study showed that allergic rhinitis, history of premature birth (<37 weeks), exclusive breastfeeding, and food allergy were factors associated with AD in Indonesian schoolchildren.